New Public Management and Hospital Performance in Algeria: Case of the University Hospital Center Benbadis in Constantine - BENELMOUFFOK, Souheila (Journal of Human Sciences, 2025)
Algerian public administration, long paralyzed by rigid and bureaucratic structures, has undertaken several reforms to modernize and play a leading role in the country's growth and prosperity. Inspired by New Public Management, a management method that emerged in the United Kingdom in the 1980s, these reforms aim to improve the efficiency of public action and redefine the role of the citizen. Despite the extension of these reforms to the hospital sector, the application of NPM at the Benbadis University Hospital Center in Constantine has not led to an improvement in the quality of care. To identify the causes of this failure, two semi-structured interviews were conducted in March 2024 with administrative officials and medical and paramedical staff of the emergency department. The study reveals that the implementation of NPM principles remained theoretical, preventing a true improvement in hospital services.